Critical Consciousness in Dual Language Bilingual Education Case Studies on Policy and Practice - Dorner, Lisa M.; Palmer, Deborah; Cervantes-Soon, Claudia; heiman, Dan; Crawford, Emily R. (Taylor & Francis, 2023)
This book features case studies that address dual language bilingual education (DLBE) programs, which offer content instruction in two languages to help youth develop fluent bilingualism/biliteracy, high academic achievement, and sociocultural competence. While increasingly popular, the DLBE model is a framework that comes with unique hurdles and challenges. Applying a pioneering critical consciousness approach, the volume provides readers with narratives, awareness, and tools to support culturally and linguistically diverse students and their families. Organized around four major areas-policy, leadership, family and community engagement, teaching and teacher learning-the volume's case studies bring together stories from policymakers, educational leaders, family and community members, and teachers. The case studies spotlight examples in which power imbalances have been identified and shifted through critically conscious actions and offer insight into how to ensure all DLBE programs are nurturing, empowering, multilingual environments for all students, particularly racialized, immigrant, and transnational students. Accessible and varied, the case studies address important topics such as anti-Black racism, digital access, disability, school-district relations, working with undocumented families, and more. Each chapter includes a case narrative, teaching notes, discussion questions, and/or teaching activities to support stakeholders who wish to develop and enact equity in their DLBE policies, classrooms, and professional development. A key resource for supporting student needs and transformative inquiry in the classroom, this book is ideal for graduate students, professors, leaders, educators, and other stakeholders in bilingual education and language education.